2004
DOI: 10.1111/j.1365-2966.2004.08368.x
|View full text |Cite
|
Sign up to set email alerts
|

Infrared mergers and infrared quasi-stellar objects with galactic winds - II. NGC 5514: two extranuclear starbursts with LINER properties and a supergiant bubble in the rupture phase

Abstract: A study of the morphology, kinematics and ionization structure of the infrared (IR) merger NGC 5514 is presented. This study is based mainly on INTEGRAL two-dimensional (2D) spectroscopy (obtained at the 4.2-m William Herschel Telescope, WHT), plus optical and near-IR images. Clear evidence of two extranuclear starbursts with young outflows (OFs) and low-ionization nuclear emission region (LINER) activity are reported. One of these OFs has generated a supergiant bubble and the other is associated with an exten… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
44
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(58 citation statements)
references
References 158 publications
(411 reference statements)
14
44
0
Order By: Relevance
“…LIER emission in merging systems shows systematically higher gas velocity dispersion compared to the stars, and, as demonstrated by the maps of velocity dispersion of gas and stars, this increase is highly localised in regions of LIER and Sy-like emission. These observations support the presence of LIER-like shock excitation in merging systems, consistently with the strong LIER-like emission observed in ULIRGs, ( most of which are strongly starbursting merging systems, largescale outflows (Lipari et al 2004) and regions at the jet-ISM interface (Cecil et al 2000). We note, however, that in the low-z Universe merging systems are extremely rare and constitute a statistically negligible part of the overall galaxy population, although they may be more commonly observed at higher redshift.…”
Section: 3supporting
confidence: 85%
“…LIER emission in merging systems shows systematically higher gas velocity dispersion compared to the stars, and, as demonstrated by the maps of velocity dispersion of gas and stars, this increase is highly localised in regions of LIER and Sy-like emission. These observations support the presence of LIER-like shock excitation in merging systems, consistently with the strong LIER-like emission observed in ULIRGs, ( most of which are strongly starbursting merging systems, largescale outflows (Lipari et al 2004) and regions at the jet-ISM interface (Cecil et al 2000). We note, however, that in the low-z Universe merging systems are extremely rare and constitute a statistically negligible part of the overall galaxy population, although they may be more commonly observed at higher redshift.…”
Section: 3supporting
confidence: 85%
“…These features are reminiscent of other systems with ‘bubbling winds’ such as the LIRG NGC 3256 (Lípari et al 2004a, see also Lípari et al 2004b). These type of flows seem to produce fragmented shells where the cool gas is already accelerated, and thus differ somewhat from the radial streamers predicted to come from stationary clumps in a steady outflow (e.g.…”
Section: Resultsmentioning
confidence: 72%
“…From 3D and 1D spectroscopic studies, we have found kinematical and morphological evidence of a close relationship between the AGN and extreme SB, in nearby ‘BAL + IR + Fe ii QSOs and mergers’ (Lípari 1994; Lípari, Colina & Macchetto 1994; Lípari et al 2000, 2003, 2004a,b,c,d, 2005a,b,c, 2006).…”
Section: Introductionmentioning
confidence: 90%